Effects of Moringa Leaf Extract on a Mouse Model of Dementia on Spatial Memory, MDA Levels, and Hippocampal Pyramidal Cell Count (CA1 & CA3) - Melati, Fitri; Purwidyaningrum, Ika; Harmastuti, Nuraini (Surya Hijau Manfaat, 2025)
Antioxidants are substances needed by the body to neutralize free radicals and prevent damage caused by free radicals. Moringa leaves contain flavanoids, alkaloids, saponins and tannins that are antioxidants because of their ability to capture free radicals. This study aims to determine the effect of moringa leaf fractions on spatial memory ability using the Radial Arm Maze method, a decrease in malondialdehyde levels and inhibition of damage to the number of hippocampal pyramidal cells in CA1 & CA3 areas. Moringa leaves were extracted using the maceration method with 70% ethanol solvent. Then the ethanol extract of Moringa leaves was fractionated using the liquid-liquid method with n-hexane, ethyl acetate and water as solvents. Next, the mice were subjected to induction treatment with lead acetate, then observed for 21 days with the Radial Arm Maze, then the mice underwent surgery and their brains were removed for MDA level testing and histopathological observation. Data were analyzed statistically using one-way ANOVA (p<0.05) followed by Tukey's test. Based on the results obtained, the ethyl acetate fraction, n-hexane fraction and water fraction can influence the improvement of spatial memory by reducing latency time and type B errors, reducing malondialdehyde levels with TBARS and inhibiting damage to CA1 and CA3 hippocampal pyramidal cells which are characterized by pknotic neuron nuclei (shriveled), dark, solid, and vacuolized.